(untitled) (Nigerian Journal of Physiological Sciences, 2021)
The root bark of Salacia nitida L.benth (celastraceae) is used as remedy for malaria and typhoid fever in Southern part of Nigeria. This study is designed to evaluate the effect of treatment with ethanolic extract from root bark of S. nitida on lipid peroxidation, hepatomegaly and splenomegaly in Plasmodium berghei-malaria infected mice. Thirty malaria-infected and six uninfected mice were used for the study. 280, 430, and 580 mg kg-1 body weight day-1 of ethanolic extract and 4 mg kg-1 body weight day-1 of artesunate were administered orally to infected mice in groups B, C, D, and E, while 4 ml kg-1 body weight day-1 of physiological saline was given to infected untreated mice in group A and the uninfected untreated mice in group F. Treatments were done for five days. Levels of malondialdehyde were measured as means of assessing lipid peroxidation in the experimental animals. Weights of experimental animals, liver, and spleen, and the length of spleen from experimental animals were also measured. Animal’s liver and spleen-body weight ratios were determined. Results from the study showed significant decrease (P < 0.05) in levels of malondialdehyde, and significant increase (P < 0.05) in body weights. Also, significant decreases (P < 0.05) were seen in the weights of liver and spleen, lengths of spleen, and organ-body weight ratios of malaria-infected treated mice. Therefore, this study confirmed that ethanolic extract from root bark of S. nitida is effective in the treatment of malaria, as it is seen in its ability to attenuate lipid peroxidation and hepatosplenomegaly in mice, thus corroborating its traditional use for the treatment of malaria.